Crystallizer and casting method for reducing cracking of high-purity alloy cast ingot by using crystallizer
By designing the inner cavity of the Lelo triangular crystallizer and optimizing the nozzle position, uniform cooling and high-purity production of high-purity alloy ingots are achieved, solving the problems of ultra-high-purity alloy thermal cracks and purity reduction, and meeting the quality requirements of the semiconductor industry.
Patent Information
- Application Number
- CN202510036758.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
AI Technical Summary
Ultra-high-purity alloys are prone to thermal cracks during rapid cooling, and the existing methods cause the alloy purity to be reduced by adding trace elements, which cannot meet the purity and quality requirements of the semiconductor industry for ultra-high-purity aluminum-copper alloys.
A crystallizer is designed, with the cross-section of the inner cavity of the crystallizer being Lylo triangle, and a heat exchange medium cavity is set between the outer shell and the inner cavity of the crystallizer. By optimizing the position and orientation of the nozzle, the molten metal liquid can achieve uniform layer cooling during the cooling process, reducing the occurrence of thermal cracks.
Through this crystallizer and casting method, the thermal crack sensitivity of high-purity alloy ingots is successfully reduced, the high purity of the alloy is ensured, and the rolling risk of the ingots is reduced. It is suitable for the production of ultra-high purity aluminum and copper sputtering targets in the semiconductor industry.
Smart Images

Figure CN119794285A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy casting, and in particular to a crystallizer and a casting method for reducing cracking of a high-purity alloy ingot by using the same. Background Art
[0002] At present, among all casting defects, cracks have a great impact on the quality of alloy products, which mainly include hot cracks and cold cracks. Hot cracks are caused by thermal stress on alloy castings during the solidification process. Thermal stress is caused by the inconsistency of thermal expansion and contraction caused by temperature changes in different parts. If the temperature change causes the stress to exceed the material's destructive strength, hot cracks will form in the casting. The main reasons for the formation of hot cracks include the following aspects: (1) The shrinkage stress is too large during the casting cooling process, and the casting is blocked during the casting process; (2) The cooling of the casting is uneven; (3) The casting structure design is unreasonable, and there are sudden changes in geometric dimensions, etc.
[0003] However, the existing methods for improving the generation of hot cracks in alloy casting mainly include adding trace elements for microalloying. For example, CN101760672A discloses a high-toughness cast aluminum-copper alloy with low hot crack sensitivity, which is alloyed by adding trace rare earth elements, specifically adding M with a mass percentage content of 0.001-1% on the basis of the base material, where M is specifically one of Ce, La, and Y or any combination thereof; although this method reduces the hot crack sensitivity of the aluminum-copper alloy and reduces the generation of hot cracks, it adds rare earth elements, which is prone to component segregation, and the addition of rare earth elements reduces the purity of the aluminum-copper alloy, which cannot meet the demand for ultra-high purity aluminum-copper alloys.
[0004] CN112626367B discloses a method for preparing a nano-alumina particle reinforced aluminum-copper alloy composite material. By reinforcing the aluminum-copper alloy with nano-alumina particles, the thermal cracking tendency of the existing aluminum-copper alloy material can be eliminated to a certain extent. However, it is also additionally doped with other elements, resulting in a decrease in the purity of the aluminum-copper alloy, which cannot meet the semiconductor industry's purity requirements for ultra-high purity aluminum-copper alloys.
[0005] However, for alloys with higher purity requirements, such as ultra-high purity copper-aluminum alloys, as the copper content increases, although the strength increases, the ductility decreases, the tendency to hot cracking increases, and through cracks are very likely to occur during the production process due to solidification shrinkage and untimely feed replenishment. For this type of ultra-high purity alloy material, adding trace elements for micro-alloying will result in the purity of the aluminum-copper alloy material not meeting the standard.
[0006] Therefore, it is urgent to develop a crystallizer and casting method that does not require the addition of other elements, ensures the purity of ultra-high purity alloys while reducing their sensitivity to thermal cracking, so as to meet the quality requirements of raw materials for ultra-high purity aluminum-copper sputtering targets for semiconductors and achieve high-quality chip production requirements. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a crystallizer and a casting method using the same to reduce cracking of high-purity alloy ingots, which solves the problem that ultra-high-purity alloys are prone to thermal cracks during rapid cooling, while ensuring the purity of the alloy. The ingots produced are not prone to rolling and are convenient for storage.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a crystallizer, comprising a crystallizer shell, a crystallizer inner cavity having a cross-section of a Lello triangle, and a heat exchange medium cavity in a gap between the crystallizer shell and the crystallizer inner cavity.
[0010] The present invention designs the shape of the crystallizer cavity, that is, designs the crystallizer cavity with a cross section of a Lello triangle, and fully utilizes the shape advantage of the Lello triangle to realize the casting of a columnar ingot with a cross section of a Lello triangle. Compared with the crystallizer cavity with a circular cross section, the outermost side of the ingot obtained by the crystallizer cavity with a cross section of a Lello triangle is the position of the three vertices of the Lello triangle. When the ingot of this shape is cooled by cooling water, it is easier to control the spraying position and direction of the heat exchange medium so that the ingot is cooled and solidified in sequence from the outermost layer to the innermost layer in all directions, thereby reducing the occurrence of thermal cracks; it avoids the traditional cylindrical ingot with consistent thickness of each layer, resulting in uneven spraying of the heat exchange medium, so that the inner layer in one direction is cooled first, and the outer layer in another direction is cooled first, thereby generating cracks due to uneven cooling; and the crystallizer cavity with a Lello triangle cross section, that is, an arc-shaped triangle, is not easy to roll and is easy to store.
[0011] Preferably, the heat exchange medium cavity is provided with at least 3 layers of uniformly distributed nozzles from top to bottom, for example, 3 layers, 4 layers or 5 layers.
[0012] Preferably, the heat exchange medium cavity is provided with three layers of uniformly distributed nozzles from top to bottom, and they are the first layer of nozzles, the second layer of nozzles and the third layer of nozzles from top to bottom.
[0013] Preferably, the first layer of nozzles includes three nozzles arranged at positions corresponding to the three vertices of the Lello triangle on the cross section.
[0014] The first layer of nozzles arranged in the heat exchange medium chamber of the crystallizer of the present invention includes three nozzles arranged at positions corresponding to the three vertices of the Léleau triangle on the cross section; the outermost layer of the ingot can be cooled first, and then cooled layer by layer towards the inner side, thereby playing a cooling buffer role and avoiding the simultaneous cooling and solidification of the inner and outer layers of the ingot, resulting in uneven cooling and thermal cracks.
[0015] Preferably, the second layer of nozzles and the third layer of water inlets independently include 3n nozzles uniformly arranged on the circumference of the inner cavity of the crystallizer, n≥2, for example, it can be 2, 3, 4, 5, 6, 7 or 8, preferably 4≤n≤8.
[0016] The present invention further preferably comprises 3n nozzles which are evenly arranged on the circumference of the inner cavity of the crystallizer, and 4≤n≤8 respectively; and they are matched with the first layer of nozzles (the three vertices of the Léau triangle) so that the outermost layer of the ingot is pre-cooled by the heat exchange medium sprayed from the first layer of nozzles, and then the ingot is cooled in all directions at the same time under the action of the heat exchange medium sprayed from the second layer of nozzles and the third layer of nozzles; thereby achieving layer-by-layer cooling from the outside to the inside and reducing the risk of cracks caused by uneven cooling.
[0017] Preferably, the angle between the direction of the nozzles of the first layer and the vertical downward direction is α, the angle between the direction of the nozzles of the second layer and the vertical downward direction is β, the direction of the nozzles of the third layer is γ, and β<α<γ.
[0018] The present invention further preferably satisfies β<α<γ, and the heat exchange medium sprayed from each nozzle works together to enable the cooling water to be sprayed evenly, and the spraying range covers the surface of the ingot. The vertices of the three Léault triangles of the ingot corresponding to the first layer of nozzles are cooled first, and then the vertices are cooled layer by layer, thereby reducing the stress generated by the simultaneous cooling of the surface of the ingot, thereby reducing the probability of through cracks.
[0019] Preferably, the angle α between the orientation of the nozzles of the first layer and the vertical downward direction is 40-50°, for example, 40°, 42°, 45°, 48° or 50°.
[0020] The present invention further preferably sets the angle α between the direction of the first layer of nozzles and the vertical downward direction to be 40-50°, so that the spray range of cooling water can evenly cover the surface of the ingot, reducing stress generation; if the corresponding angle α is too small, the spray range of cooling water will be incomplete, resulting in uneven cooling of the ingot and easy cracking; if the corresponding angle α is too large, the cooling intensity at the first layer of nozzles will be too large, and the stepped cooling effect will not be achieved.
[0021] Preferably, the angle β between the direction of the second layer nozzle and the vertical downward direction is 15-25°, for example, 15°, 18°, 20°, 23° or 25°.
[0022] Preferably, the angle γ between the direction of the nozzle of the third layer and the vertical downward direction is 60-70°, for example, 60°, 62°, 65°, 68° or 70°.
[0023] The present invention further preferably sets the angle β between the direction of the second layer of nozzles and the vertical downward direction to be 15-25°, and the angle γ between the direction of the third layer of nozzles and the vertical downward direction to be 60-70°. Together with the first layer of nozzles, they work together to make the alloy melt cool more evenly when it passes through the crystallizer, and the temperature of the ingot decreases in a step-by-step manner, thereby reducing the cracking of high-purity alloys with high thermal cracking sensitivity.
[0024] Preferably, the crystallizer further comprises a material receiving component and a heat-insulating component.
[0025] Preferably, the heat-insulating component comprises a graphite ring.
[0026] The present invention further preferably provides a graphite ring between the material receiving component and the crystallizer. Since graphite has good thermal conductivity and heat preservation properties, it helps to maintain the temperature inside the crystallizer, reduce thermal shock caused by rapid temperature changes, and reduce the risk of cracks in the ingot.
[0027] Preferably, the heat-insulating component is arranged on the top of the inner cavity of the crystallizer having a Lello triangle cross section.
[0028] Preferably, the material receiving component is arranged on the top of the heat insulation component.
[0029] In a second aspect, the present invention provides a casting method for reducing cracking of high-purity alloy ingots, wherein the casting method is performed using the crystallizer described in the first aspect.
[0030] The casting method for reducing cracking of high-purity alloy ingots provided by the present invention is carried out using the crystallizer described in the first aspect, thereby achieving uniform cooling and solidification of the alloy melt, and the temperature in the crystallization cavity decreases in a step-by-step manner. No new elements need to be added for micro-alloying, thereby reducing product cracking and successfully preparing high-quality ultra-high-purity alloy ingot products, providing high-quality raw materials for the semiconductor chip industry.
[0031] Preferably, the casting method comprises the following steps:
[0032] The molten metal liquid is poured into the crystallizer, and the molten metal liquid is cooled by the cooling water in the heat exchange medium cavity until solidification, thereby completing the casting.
[0033] Since multiple phases will be generated during the casting process of AlCu alloys, such as the solid solution of Cu in Al, theta phase, etc., the precipitation of theta phase can easily become the starting point of cracks, especially during rapid cooling. Therefore, the AlCu alloy has a high sensitivity to hot cracking, especially the copper content has a great influence on its hot cracking sensitivity. With the increase of copper content, the strength of the AlCu alloy increases, but the ductility decreases and the tendency to hot cracking increases. To solve this problem, the present invention provides a casting method for reducing the cracking of high-purity AlCu alloy ingots, and the composition of the AlCu alloy is Al: 99.2-99.6wt%, Cu: 0.3-0.7wt%, and the rest are unavoidable impurities, in terms of mass percentage.
[0034] Preferably, the pouring temperature of the molten metal is 675-720°C, for example, it can be 675°C, 680°C, 685°C, 690°C, 695°C, 700°C, 710°C or 720°C.
[0035] Preferably, the pouring speed is 90-120 mm / min, for example, it can be 90 mm / min, 95 mm / min, 100 mm / min, 105 mm / min, 110 mm / min, 115 mm / min or 120 mm / min.
[0036] Preferably, the temperature of the cooling water is 15-25°C, for example, 15°C, 17°C, 19°C, 20°C, 22°C or 25°C.
[0037] Preferably, the total flow rate of the cooling water is 480-520 L / min, for example, it can be 480 L / min, 490 L / min, 500 L / min, 510 L / min or 520 L / min.
[0038] The present invention further preferably sets the total flow rate of the cooling water to 480-520 L / min, which is beneficial to ensure a suitable cooling rate, reduce the generation of thermal stress, ensure uniform grain structure of the ingot and high surface quality; if the total flow rate of the cooling water is too low, insufficient cooling will result; if the total flow rate of the cooling water is too high, the cooling rate will be too fast, thermal stress will increase, and the quality of the ingot will decrease.
[0039] As a further preferred technical solution of the present invention, the casting method comprises the following steps:
[0040] The molten metal is poured into the crystallizer at a pouring temperature of 675-720°C and a pouring speed of 90-120 mm / min. At the same time, cooling water at 15-25°C is sprayed from the first layer of nozzles into the inner cavity of the crystallizer at a direction of 40-50° to the vertical downward direction, from the second layer of nozzles into the inner cavity of the crystallizer at a direction of 15-25° to the vertical downward direction, and from the third layer of nozzles into the inner cavity of the crystallizer at a direction of 60-70° to the vertical downward direction, until the molten metal solidifies into an ingot and the casting is completed; the total flow rate of the cooling water is 480-520 L / min.
[0041] Compared with the prior art, the present invention has at least the following beneficial effects:
[0042] (1) The crystallizer provided by the present invention has an inner cavity of the crystallizer with a cross-section of a Léleau triangle, and the position and direction of the nozzle are further optimized, so that the temperature of the molten metal liquid decreases in a step-by-step manner when it is cooled and solidified in the inner cavity of the crystallizer, thereby achieving a uniform cooling effect and avoiding thermal cracks caused by thermal stress due to temperature changes. In addition, the inner cavity structure of the crystallizer with a cross-section of a Léleau triangle makes the obtained ingot difficult to roll and easy to store.
[0043] (2) The casting method for reducing cracking of high-purity alloy ingots provided by the present invention is carried out using the above-mentioned crystallizer, and by further controlling the spraying direction of the cooling water and the total flow rate and other process parameters, the thermal cracking sensitivity of the high-purity alloy ingots is further reduced. No additional element microalloying is required, and the generation of microcracks can be reduced. The proportion of cracked ingot length is preferably as low as less than 5.30%. Moreover, the high purity of the obtained product is guaranteed and it is easy to store. The casting method has a simple operation process and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a front view structural schematic diagram of the crystallizer provided in Example 1 of the present invention;
[0045] Figure 2 1 is a schematic diagram of the cross section of the inner cavity of the crystallizer and the nozzle position distribution of the first layer of nozzles provided in Example 1 of the present invention;
[0046] Figure 3 Schematic diagram of the orientation of nozzles at each layer in the crystallizer provided in Example 1 of the present invention;
[0047] Figure 4 Schematic diagram of nozzle position distribution of the first layer of nozzles in the crystallizer provided in Example 7 of the present invention;
[0048] In the figure: 1. crystallizer shell; 2. crystallizer cavity; 3. first layer nozzle; 31. nozzle A; 32. nozzle B; 33. nozzle C; 4. second layer nozzle; 5. third layer nozzle; 6. graphite ring; 7. receiving trough. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0050] The molten aluminum-copper liquid used in the following examples contains 99.4 wt% Al and 0.5 wt% Cu, with the remainder being unavoidable impurities.
[0051] 1. Implementation
[0052] Example 1
[0053] This embodiment provides a crystallizer, such as Figure 1 and Figure 2 As shown, the crystallizer comprises a crystallizer shell 1, a crystallizer inner cavity 2 having a cross section of a Lello triangle, and a heat exchange medium cavity in the gap between the crystallizer shell 1 and the crystallizer inner cavity 2; the heat exchange medium is cooling water;
[0054] The heat exchange medium cavity is provided with three layers of uniformly distributed nozzles from top to bottom, and the nozzles are the first layer 3, the second layer 4 and the third layer 5 from top to bottom;
[0055] The first layer of nozzles 3 includes three nozzles arranged at positions corresponding to the three vertices of the Lello triangle on the cross section, namely nozzle A 31, nozzle B 32 and nozzle C 33;
[0056] The second layer of nozzles 4 and the third layer of water nozzles each independently include 18 nozzles evenly arranged on two sides of the inner cavity of the crystallizer;
[0057] like Figure 3 As shown, the angle α between the first layer nozzle 3 and the vertical downward direction is 45°, the angle β between the second layer nozzle 4 and the vertical downward direction is 20°, and the angle γ between the third layer nozzle 5 and the vertical downward direction is 65°;
[0058] The crystallizer further includes a material receiving trough 7 and a graphite ring 6 ; the graphite ring 6 is arranged at the top of the crystallizer inner cavity 2 whose cross section is a Lello triangle; the material receiving trough 7 is arranged at the top of the graphite ring 6 .
[0059] This embodiment provides a casting method for reducing cracking of a high-purity aluminum-copper alloy ingot. The casting method is performed using the above-mentioned crystallizer and comprises the following steps:
[0060] The molten aluminum-copper liquid is poured into the crystallizer at a pouring temperature of 690°C and a pouring speed of 100 mm / min. At the same time, cooling water at 20°C is sprayed from the first layer nozzle 3 to the inner cavity 2 of the crystallizer at a direction of 45° to the vertical downward direction, from the second layer nozzle 4 to the inner cavity 2 of the crystallizer at a direction of 20° to the vertical downward direction, and from the third layer nozzle 5 to the inner cavity 2 of the crystallizer at a direction of 65° to the vertical downward direction, until the molten aluminum-copper liquid solidifies into an ingot and the casting is completed; the total flow rate of the cooling water is 500 L / min.
[0061] Example 2
[0062] This embodiment provides a crystallizer, the crystallizer comprising a crystallizer shell, a crystallizer inner cavity having a cross section of a Lello triangle, and a heat exchange medium cavity in the gap between the crystallizer shell and the crystallizer inner cavity; the heat exchange medium is cooling water;
[0063] The heat exchange medium cavity is provided with three layers of uniformly distributed nozzles from top to bottom, and the nozzles are the first layer, the second layer and the third layer from top to bottom;
[0064] The first layer of nozzles includes three nozzles arranged at positions corresponding to the three vertices of the Lello triangle on the cross section;
[0065] The second layer of nozzles and the third layer of water nozzles each independently include 15 nozzles evenly arranged on the circumference of the inner cavity of the crystallizer;
[0066] The angle α between the first layer of nozzles and the vertical downward direction is 40°, the angle β between the second layer of nozzles and the vertical downward direction is 15°, and the angle γ between the third layer of nozzles and the vertical downward direction is 60°;
[0067] The crystallizer further comprises a material receiving trough and a graphite ring; the graphite ring is arranged at the top of the inner cavity of the crystallizer with a cross section in the shape of a Lello triangle; the material receiving trough is arranged at the top of the graphite ring.
[0068] This embodiment provides a casting method for reducing cracking of a high-purity aluminum-copper alloy ingot. The casting method is performed using the above-mentioned crystallizer and comprises the following steps:
[0069] The molten aluminum-copper liquid is poured into the crystallizer at a pouring temperature of 675°C and a pouring speed of 90 mm / min. At the same time, cooling water at 15°C is sprayed from the first layer of nozzles to the inner cavity of the crystallizer at a direction of 40° to the vertical downward direction, from the second layer of nozzles to the inner cavity of the crystallizer at a direction of 15° to the vertical downward direction, and from the third layer of nozzles to the inner cavity of the crystallizer at a direction of 60° to the vertical downward direction, until the molten aluminum-copper liquid solidifies into an ingot and the casting is completed; the total flow rate of the cooling water is 480 L / min.
[0070] Example 3
[0071] This embodiment provides a crystallizer, the crystallizer comprising a crystallizer shell, a crystallizer inner cavity having a cross section of a Lello triangle, and a heat exchange medium cavity in the gap between the crystallizer shell and the crystallizer inner cavity; the heat exchange medium is cooling water;
[0072] The heat exchange medium cavity is provided with three layers of uniformly distributed nozzles from top to bottom, and the nozzles are the first layer, the second layer and the third layer from top to bottom;
[0073] The first layer of nozzles includes three nozzles arranged at positions corresponding to the three vertices of the Lello triangle on the cross section;
[0074] The second layer of nozzles and the third layer of water nozzles each independently include 24 nozzles evenly arranged on the circumference of the inner cavity of the crystallizer;
[0075] The angle α between the first layer of nozzles and the vertical downward direction is 50°, the angle β between the second layer of nozzles and the vertical downward direction is 25°, and the angle γ between the third layer of nozzles and the vertical downward direction is 70°;
[0076] The crystallizer further comprises a material receiving trough and a graphite ring; the graphite ring is arranged at the top of the inner cavity of the crystallizer with a cross section in the shape of a Lello triangle; the material receiving trough is arranged at the top of the graphite ring.
[0077] This embodiment provides a casting method for reducing cracking of a high-purity aluminum-copper alloy ingot. The casting method is performed using the above-mentioned crystallizer and comprises the following steps:
[0078] The molten aluminum-copper liquid is poured into the crystallizer at a pouring temperature of 720°C and a pouring speed of 120 mm / min. At the same time, cooling water at 25°C is sprayed from the first layer of nozzles into the inner cavity of the crystallizer at a direction of 50° to the vertical downward direction, from the second layer of nozzles into the inner cavity of the crystallizer at a direction of 25° to the vertical downward direction, and from the third layer of nozzles into the inner cavity of the crystallizer at a direction of 70° to the vertical downward direction, until the molten aluminum-copper liquid solidifies into an ingot, completing the casting; the total flow rate of the cooling water is 520 L / min.
[0079] Example 4
[0080] This embodiment provides a crystallizer, which is the same as that of Embodiment 1 except that the angle between the orientation of the first layer nozzle and the vertical downward direction is 55°.
[0081] This embodiment provides a casting method for reducing cracking of high-purity aluminum-copper alloy ingots. The casting method is the same as Embodiment 1 except that the crystallizer provided in this embodiment is used.
[0082] Example 5
[0083] This embodiment provides a crystallizer, which is the same as that of Embodiment 1 except that the angle between the orientation of the first layer nozzle and the vertical downward direction is 35°.
[0084] This embodiment provides a casting method for reducing cracking of high-purity aluminum-copper alloy ingots. The casting method is the same as Embodiment 1 except that the crystallizer provided in this embodiment is used.
[0085] Example 6
[0086] This embodiment provides a crystallizer, which is the same as Embodiment 1 except that the first layer of nozzles is not provided, and only the second layer of nozzles and the third layer of nozzles are provided.
[0087] This embodiment provides a casting method for reducing cracking of high-purity aluminum-copper alloy ingots. The casting method is the same as Embodiment 1 except that the crystallizer provided in this embodiment is used.
[0088] Example 7
[0089] This embodiment provides a crystallizer, wherein the crystallizer has the first layer of nozzles distributed at positions corresponding to the midpoints of the three arcs of the Leraud triangle in the cross section (such as Figure 4 Except for the above, the rest are the same as those in Example 1.
[0090] This embodiment provides a casting method for reducing cracking of high-purity aluminum-copper alloy ingots. The casting method is the same as Embodiment 1 except that the crystallizer provided in this embodiment is used.
[0091] Example 8
[0092] This embodiment provides a crystallizer, which is the same as that of Embodiment 1 except that the number and position distribution of the first layer nozzles and the second layer nozzles are the same.
[0093] This embodiment provides a casting method for reducing cracking of high-purity aluminum-copper alloy ingots. The casting method is the same as Embodiment 1 except that the crystallizer provided in this embodiment is used.
[0094] Example 9
[0095] This embodiment provides a crystallizer, in which the first layer of nozzles, the second layer of nozzles and the third layer of nozzles are all oriented at an angle of 65° to the vertical downward direction, and the rest are the same as those in Embodiment 1.
[0096] This embodiment provides a casting method for reducing cracking of high-purity aluminum-copper alloy ingots. The casting method is the same as Embodiment 1 except that the crystallizer provided in this embodiment is used.
[0097] Example 10
[0098] This embodiment provides a casting method for reducing cracking of high-purity aluminum-copper alloy ingots. The casting method is the same as Example 1 except that the total flow rate of cooling water is 450 L / min.
[0099] Embodiment 11
[0100] This embodiment provides a casting method for reducing cracking of high-purity aluminum-copper alloy ingots. The casting method is the same as Example 1 except that the total flow rate of cooling water is 550 L / min.
[0101] 2. Comparison
[0102] Comparative Example 1
[0103] This comparative example provides a crystallizer, which is the same as Example 1 except that the cross-section of the inner cavity of the crystallizer is circular.
[0104] This comparative example provides a casting method for a high-purity aluminum-copper alloy ingot. The casting method is the same as Example 1 except that the crystallizer provided in this comparative example is used.
[0105] Comparative Example 2
[0106] This comparative example provides a crystallizer, which is the same as Example 1 except that the cross-section of the inner cavity of the crystallizer is triangular.
[0107] This comparative example provides a casting method for a high-purity aluminum-copper alloy ingot. The casting method is the same as Example 1 except that the crystallizer provided in this comparative example is used.
[0108] 3. Test and its results
[0109] The high-purity aluminum-copper alloy ingots obtained by the casting methods provided in the above embodiments and comparative examples were detected using a flaw detector (Shanghai Yace Instrument Technology Co., Ltd., CUT-Q5). The cracked parts, i.e., the cracked ingots, were cut and scrapped, and the ratio of the length of the cracked ingot to the length of the entire ingot, i.e., the cracked ingot length ratio, was calculated. The results are shown in Table 1.
[0110] Table 1
[0111] project Crack ingot length ratio / % Example 1 5.12 Example 2 5.30 Example 3 5.24 Example 4 7.33 Example 5 7.54 Example 6 8.74 Example 7 8.66 Example 8 9.45 Example 9 10.44 Example 10 12.31 Embodiment 11 13.62 Comparative Example 1 14.25 Comparative Example 2 14.33
[0112] From Table 1 we can see that:
[0113] (1) It can be seen from Examples 1 to 3 that the crystallizer provided by the present invention and the casting method for reducing cracking of high-purity alloy ingots using the same reduce the possibility of cracking of high-purity aluminum-copper alloy ingots, successfully produce high-quality high-purity aluminum-copper alloy ingots, and the cracked ingot length accounts for less than 5.30%, thereby improving the qualified production efficiency and meeting the quality requirements of raw materials for ultra-high purity sputtering targets for semiconductors.
[0114] (2) Combining Example 1 with Examples 4 to 5, it can be seen that since the angle between the direction of the first layer of nozzles in the crystallizer used in Examples 4 and 5 and the vertical downward direction is too small or too large, it leads to uneven temperature changes during cooling and solidification, resulting in thermal cracks, and the flaw detection pass rate of the same batch of products is reduced; therefore, the present invention further preferably sets the angle between the direction of the first layer of nozzles in the crystallizer and the vertical downward direction to 40 to 50 degrees, which further improves the uniformity of cooling, thereby reducing the generation of cracks and improving the flaw detection pass rate of the same batch of products.
[0115] (3) Combining Example 1 with Examples 6 to 9, it can be seen that since the first layer of nozzles is not provided in Example 6, that is, there is no cooling buffer, a large number of cracks are generated, and the cracked ingot length ratio increases to 8.74%; in Example 7, the first layer of nozzles is distributed at the positions corresponding to the midpoints of the three arcs of the Lelo triangle section, resulting in the inability to start cooling from the outermost layer, uneven cooling inside and outside, resulting in a large number of thermal cracks, and the cracked ingot length ratio increases to 8.66%; in Example 8, the crystallizer has the same number and position distribution of the first layer of nozzles and the second layer of nozzles, and the cooling buffer effect cannot be achieved. Cracks are generated, and the proportion of cracked ingot length increases to 9.45%; in the crystallizer described in Example 9, the angles between the first layer of nozzles, the second layer of nozzles and the third layer of nozzles and the vertical downward direction are all 65°, and the inclination angles of the three layers of nozzles are the same, resulting in uneven cooling, thereby generating cracks, and the proportion of cracked ingot length increases to 10.44%; this shows that the present invention further optimizes the nozzle position and orientation of the crystallizer, further improves the uniformity of cooling, makes the temperature of the ingot decrease in a step-by-step manner during the solidification process, reduces the generation of thermal cracks, and improves the flaw detection pass rate of the same batch of products.
[0116] (4) Combining Example 1, Example 10 and Example 11, since the total flow rate of cooling water in Example 10 is too small, thermal cracks are generated in the ingot, and the cracked ingot length accounts for 12.31%; the total flow rate of cooling water in Example 11 is too large, which causes thermal cracks to be generated in the ingot, and the cracked ingot length accounts for 13.62%; this shows that the present invention further prefers that the flow rate of cooling water is 480-520L / min, which further reduces the generation of ingot cracks and improves the flaw detection pass rate of the same batch of products.
[0117] (5) It can be seen from Example 1 and Comparative Examples 1 to 2 that, since the cross-section of the crystallization cavity of the crystallizer in Comparative Example 1 is circular, the proportion of cracked ingot length increases to 14.25%, and the product is easy to roll and difficult to store; the cross-section of the crystallization cavity of the crystallizer in Comparative Example 2 is triangular, which is easy to store, but has many cracks, and the proportion of cracked ingot length increases to 14.33%; the production efficiency is greatly reduced.
[0118] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A crystallizer, characterized in that: The crystallizer comprises a crystallizer shell, a crystallizer inner cavity with a cross section of a Lello triangle, and a heat exchange medium cavity at a gap position between the crystallizer shell and the crystallizer inner cavity.
2. The crystallizer according to claim 1, characterized in that The heat exchange medium cavity is provided with at least three layers of nozzles evenly distributed from top to bottom.
3. The crystallizer according to claim 1 or 2, characterized in that The heat exchange medium cavity is provided with three layers of uniformly distributed nozzles from top to bottom, and the nozzles are the first layer, the second layer and the third layer from top to bottom; Preferably, the first layer of nozzles includes three nozzles arranged at positions corresponding to the three vertices of the Lello triangle on the cross section; Preferably, the second layer of nozzles and the third layer of nozzles each independently include 3n nozzles uniformly arranged on the circumference of the inner cavity of the crystallizer, n≥2, preferably 4≤n≤8.
4. The crystallizer according to claim 3, characterized in that The angle between the first layer of nozzles and the vertical downward direction is α, the angle between the second layer of nozzles and the vertical downward direction is β, the angle between the third layer of nozzles and the vertical downward direction is γ, and β<α<γ; Preferably, the angle α between the direction of the first layer nozzle and the vertical downward direction is 40-50°; Preferably, the angle β between the direction of the second layer nozzle and the vertical downward direction is 15-25°; Preferably, the angle γ between the direction of the nozzle of the third layer and the vertical downward direction is 60-70°.
5. The crystallizer according to any one of claims 1 to 4, characterized in that: The crystallizer also includes a material receiving component and a heat preservation component; Preferably, the heat-insulating component comprises a graphite ring; Preferably, the heat-insulating component is arranged on the top of the inner cavity of the crystallizer having a Lello triangle cross section; Preferably, the material receiving component is arranged on the top of the heat insulation component.
6. A casting method for reducing cracking of high-purity alloy ingots, characterized in that: The casting method is carried out using the crystallizer as described in any one of claims 1 to 5.
7. The casting method according to claim 6, characterized in that: The casting method comprises the following steps: The molten metal liquid is poured into the crystallizer, and the molten metal liquid is cooled by the cooling water in the heat exchange medium cavity until solidification, thereby completing the casting.
8. The casting method according to claim 6 or 7, characterized in that: The pouring temperature of the molten metal is 675-720°C; Preferably, the pouring speed is 90-120 mm / min.
9. The casting method according to any one of claims 6 to 8, characterized in that: The temperature of the cooling water is 15-25°C; Preferably, the total flow rate of the cooling water is 480-520 L / min.
10. The casting method according to any one of claims 6 to 9, characterized in that: The casting method comprises the following steps: The molten metal is poured into the crystallizer at a pouring temperature of 675-720°C and a pouring speed of 90-120 mm / min. At the same time, cooling water at 15-25°C is sprayed from the first layer of nozzles into the inner cavity of the crystallizer at a direction of 40-50° to the vertical downward direction, from the second layer of nozzles into the inner cavity of the crystallizer at a direction of 15-25° to the vertical downward direction, and from the third layer of nozzles into the inner cavity of the crystallizer at a direction of 60-70° to the vertical downward direction, until the molten metal solidifies into an ingot and the casting is completed; the total flow rate of the cooling water is 480-520 L / min.
Citation Information
Patent Citations
Low heat track sensitive high-toughness casting aluminium copper alloy
CN101760672A
Preparation method of nano-alumina particle reinforced aluminum-copper alloy composite material
CN112626367B